2019
DOI: 10.26442/00403660.2019.03.000101
|View full text |Cite
|
Sign up to set email alerts
|

Features of the current of bronchial asthma in the presence of komorbidy allergic rhinitis

Abstract: Aim - study of the influence of komorbidy allergic rhinitis (AR) on the course of bronchial asthma (BA). Materials and methods. Clinical research, single performed by a survey of 96 patients divided into two groups: the main - 73 patients with BA combined with AR and a group of comparison-23 patients who do not have allergic rhinitis. The data of clinic, bronchial passableness, level of control of asthma, severity of inflammation in bronhopulmonary region on content of nitrogen oxide in exhaled air and in nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Based on statistical data, a significant percentage of children, ranging from 29% to 35%, who suffer from atopic dermatitis exhibit a susceptibility to developing allergic bronchial asthma [ 12 ]. Moreover, previous studies have demonstrated a significant correlation between atopic dermatitis and rhinitis in children, which substantially increases their susceptibility (about 99.3%) to the development of allergic bronchial asthma.…”
Section: Extra-cutaneous Clinical Manifestations Among Different Racesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on statistical data, a significant percentage of children, ranging from 29% to 35%, who suffer from atopic dermatitis exhibit a susceptibility to developing allergic bronchial asthma [ 12 ]. Moreover, previous studies have demonstrated a significant correlation between atopic dermatitis and rhinitis in children, which substantially increases their susceptibility (about 99.3%) to the development of allergic bronchial asthma.…”
Section: Extra-cutaneous Clinical Manifestations Among Different Racesmentioning
confidence: 99%
“…It is noteworthy that this condition is also noticed in persons diagnosed with atopic dermatitis. However, it has lately been incorporated into the diagnostic criteria for asthma [ 12 ] The experiment indicated above, and its corresponding findings suggest a notable similarity in the pathophysiology of allergic bronchial asthma and atopic dermatitis. Both disorders are predominantly attributed to aeroallergens, and the symptoms of atopic dermatitis can be intensified by either exposure to or direct contact with these allergens.…”
Section: Extra-cutaneous Clinical Manifestations Among Different Racesmentioning
confidence: 99%
“…Statistically, 29–35% of children with atopic dermatitis develop allergic bronchial asthma, and children with atopic dermatitis who contract rhinitis have a significantly higher risk (99.3% of developing allergic bronchial asthma). An important aspect in the pathophysiology of asthma is bronchial hyper-reactivity, which is also present in patients with atopic dermatitis but absent in the criteria for a diagnosis of asthma [ 28 , 29 ].…”
Section: Extra-cutaneous Clinical Manifestationsmentioning
confidence: 99%
“…A vast Danish research study demonstrated associations between a mutation on the gene that encodes protocadherin-1 (PCDH1) and asthma, wheezing, and atopic dermatitis in children. An interaction between PCDH-1 and passive exposure to smoke during childhood in the development of asthma was also suggested [ 29 ]. Other studies emphasized the correlation among the age of onset for atopic dermatitis, its severity, and the appearance of asthma and allergic rhinitis.…”
Section: Extra-cutaneous Clinical Manifestationsmentioning
confidence: 99%